Statistical theory of diffusion-reaction processes in the system “metal-adsorbate-gas” - Kostrobii, P.P.; Markovych, B.M.; Rudavskii, Yu.K.; Tokarchuk, M.V. (Condensed Matter Physics, 2001)
We present a statistical theory for diffusion-reaction processes of gaseous
mixture in the system “metal-adsorbate-gas”. The theory is based on an
equal consideration of electron-electron, electron-atom and atom-atom interactions
between adsorbed, non-adsorbed atoms and atoms of metal
surface. On a metal surface, the bimolecular reactions of the A + B ↔ AB
type are possible between the adsorbed atoms which is typical of catalytic
processes. By means of Zubarev nonequilibrium statistical operator, the
system of transport equations is obtained for a consistent description of
electronic kinetic and diffusion-reaction atomic processes. Ми представляємо статистичну теорію дифузійно-реакційних процесів для газових сумішей в системі “метал-адсорбат-газ”. Теорія базується на рівноправному врахуванні електрон-електронних,
електрон-атомних та атом-атомних взаємодій між адсорбованими
та неадсорбованими атомами і атомами поверхні металу. На поверхні металу між адсорбованими атомами можуть проходити бімолекулярні реакції A + B ↔ AB. Застосувавши метод нерівноважного статистичного оператора Зубарєва, ми отримали систему рівнянь
переносу для узгодженого опису кінетики електронів та дифузійнореакційних атомних процесів.